Intragastric and atomized administration of canagliflozin inhibit inflammatory cytokine storm in lipopolysaccharide-treated sepsis in mice: A potential COVID-19 treatment - Niu, Yaoyun (Int Immunopharmacol, 2021)
To date, drugs to attenuate cytokine storm in severe cases of Corona Virus Disease 2019 (COVID-19) are not available. In this study, we investigated the effects of intragastric and atomized administration of canagliflozin (CAN) on cytokine storm in lung tissues of lipopolysaccharides (LPS)-induced mice. Results showed that intragastric administration of CAN significantly and widely inhibited the production of inflammatory cytokines in lung tissues of LPS-induced sepsis mice. Simultaneously, intragastric administration of CAN significantly improved inflammatory pathological changes of lung tissues. Atomized administration of CAN also exhibited similar effects in LPS-induced sepsis mice. Furthermore, CAN significantly inhibited hypoxia inducible factor 1α (HIF-1α) and phosphofructokinase-2/fructose-2,6-bisphosphatase 3 (PFKFB3) protein levels in LPS-treated lung tissues. These results indicated that CAN might attenuate cytokine storm and reduce the inflammatory symptoms in critical cases in COVID-19. Its action mechanism might involve the regulation of HIF-1α and glycolysis in vivo. However, further studies about clinical application and mechanism analysis should be validated in the future.